PARTISIPASI MASYARAKAT DALAM PENGEMBANGAN KAWASAN TRANSMIGRASI REMPANG ECO-CITY - Fince Aulia; Retna Hanani (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2026)
This research is motivated by the development of the Rempang Eco-City Transmigration Area as part of the National Strategic Project (PSN). The program has generated social dynamics related to transmigrant community participation in development and relocation processes. The area development aims to increase economic growth and investment. However, community involvement is essential to ensure policy legitimacy and sustainability. This study aims to analyze community participation in the development of the transmigration area and to identify the supporting and inhibiting factors. The research employs a descriptive qualitative method. Data were collected through in-depth interviews, observation, documentation, and literature review. The informants consist of BP Batam, the Rempang Eco-City Transmigration Area Development Working Unit, community leaders, local transmigrant fishermen, transmigrant residents, and academics. Data were analyzed through data reduction, data display, and verification using triangulation techniques. The results show that community participation remains dominant at the levels of information and consultation. Participation at the stages of deciding together, acting together, and supporting community is not yet optimal. Supporting factors include community willingness, capacity, and opportunity to participate. Inhibiting factors include stakeholder dominance, limited educational background, differences in age and gender, and livelihoods affected by relocation. This study concludes that more inclusive and collaborative participation mechanisms are needed. Transmigrant communities should become subjects of development rather than merely objects of policy.